Computed torque control of a 2-RR planar parallel robot (2017)
The design, construction and control of a two degree-of-freedom planar mechanism with five bar and five joints are presented. Computed control torque strategy in the joint space was implemented in order to fulfill a kinematic task by the end effector. It was required the position and velocity kinematic full analysis of the robot, both direct and reverse. The control law needed only the acceleration reverse kinematic formulation. The dynamic model of this parallel robot was obtained using an advantageous approach that is typical of serial robots, making easier the non-linear control techniques implementation. The validity of the dynamic model approach and the functionality of the controller are experimentally verified in the generation of a circular path by the end effector. Although there is accordance between the simulation and the experimental results, future work to implement other non-linear control strategies are suggested given the no modeled effects present in the system.